Faith and Friction: Underlying Causes of Religious Conflicts in 21st Century - Naz, Dr. Uzma; Naeem, Shahid (South Asian Journal of Religion and Philosophy (SAJRP), 2025)
Religious wars have existed since the beginning of the humankind and in the 21st century they have also become more complicated and intense because of the globalization process, technological discovery, socio-political changes and the cultural identity crisis. This paper digs deeper into the background of modern religious wars by investigating motives which include political factors, cultural and historical aspects and identity issues. The main objective of the research is to examine the interaction of all these varying issues that promote tensions between various religious groups in various regions. This will help to gain additional insight into the nature of religious conflicts and how they can develop into violence. Areas of the research include the importance of struggle for political power, resource-related rivalries, past resentments, social inequalities, media interventions and the fear of identity-loss, which have all been key factors leading to the continuation and stretching of religious wars. This article has a qualitative approach since it is based on the use of case studies located in different regions of the globe to study the patterns and dynamics of religious conflict. It also has a multi-theoretical approach that integrates Social Identity Theory, Relative Deprivation Theory and Instrumentalism to analyse the psychological, social and political aspects of these conflicts. Research indicates that religious conflict does not have one definite cause but is a result of an interplay of structural inequalities, political exploitation, and cultural unwillingness to change as well as the globalization of ideas and stories. In this research, the current technologies of communication serve two purposes, which include the contribution to the emergence of tensions and the possibility of creating a dialogue. This paper can contribute to the process of policy-making, interfaith interaction and peacebuilding across an increasingly interconnected yet fragmented world by uncovering major causes of religious conflict and the implications of dealing with them.